(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article investigates the thematic roles of blessings as speech acts in the Uzbek language, with specific focus on examples extracted from the works of renowned Uzbek writer A. Kahhar. The study aims to analyze the linguistic characteristics and cultural significance of expressing blessings in Uzbek, and to explore how these speech acts contribute to social interactions and the construction of meaning within the language. Blessings represent a meaningful linguistic construct through which the speaker conveys their affective states and evaluative attitudes toward the interlocutor. The semantic interpretation of these expressions relies on the presupposition of mutually shared background knowledge between the speaker and the hearer. Blessings, often categorized as good wishes, are a prevalent type of speech act observed across various languages. Influenced by cultural and social factors, many expressions of blessings have undergone semantic shift, losing their literal interpretation and functioning as idiomatic or conventionalized expressions within specific linguistic communities.